Annual report ... -2012- - Raynor, Kyla (Government of Bermuda. Ministry of Justice. Department for National Drug Control BM, 2012)
Serves a a monitoring mechanism of the progress made in reducing the demand and supply associated with both the licit and illicit drug trade. Provides a comprehensive tabular representation of the drug situation within Bermuda - from importation of alcohol and tobacco products and persons in substance abuse treatment to prosecutions for drug-related offences.